2018
DOI: 10.1089/acm.2017.0184
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Medical Marijuana over Prescription Medications Among Persons Living with Chronic Conditions: Alternative, Complementary, and Tapering Uses

Abstract: MC appears to serve as both a complementary method for symptom management and treatment of medication side-effects associated with certain chronic conditions, and as an alternative method for treatment of pain, seizures, and inflammation in this population. Additional patient-centered research is needed to identify specific dosing patterns of MC products associated with symptom alleviation and produce longitudinal data assessing chronic disease outcomes with MC use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
1
38
0
4
Order By: Relevance
“…The most common form of MC consumption was inhalation (reported in 35 studies), either via smoking (joint or blunt, joint with tobacco, pipe, water pipe) or vaping (vaporizer) [34, 36, 51, 58-63, 65, 68-70, 72, 74-86, 88, 92, 94-97, 99, 101]. Reported smoking prevalence ranged from 20% [85] to 91% [59] and vaping prevalence from 7% [60] to 53% [78]. Ingested (cannabis tea, baked goods, oils, tinctures, tablets and capsules) [51, 58-61, 63, 65, 67-70, 72, 75, 76, 80-83, 85, 86, 88, 95, 97, 99] and topical administration [58,59,63,75,80,99] were less common forms of MC use (reported in 25 and 6 studies, respectively).…”
Section: Patterns Of MC Usementioning
confidence: 99%
See 2 more Smart Citations
“…The most common form of MC consumption was inhalation (reported in 35 studies), either via smoking (joint or blunt, joint with tobacco, pipe, water pipe) or vaping (vaporizer) [34, 36, 51, 58-63, 65, 68-70, 72, 74-86, 88, 92, 94-97, 99, 101]. Reported smoking prevalence ranged from 20% [85] to 91% [59] and vaping prevalence from 7% [60] to 53% [78]. Ingested (cannabis tea, baked goods, oils, tinctures, tablets and capsules) [51, 58-61, 63, 65, 67-70, 72, 75, 76, 80-83, 85, 86, 88, 95, 97, 99] and topical administration [58,59,63,75,80,99] were less common forms of MC use (reported in 25 and 6 studies, respectively).…”
Section: Patterns Of MC Usementioning
confidence: 99%
“…Following MC use, a signi cant proportion of study participants (24% to 95%) reported considerable alleviation of pain, headache, and anxiety [34, 36, 52, 54, 55, 57, 60-65, 68, 70-73, 75-77, 80-84, 86-88, 91-97, 99] (Table 1). In addition, they perceived positive effects on mood, and an improvement of their general quality of life [18,60,65,74,82,91,96]. Participants also reported longer effects of MC with milder adverse effects, as compared to opioids and other prescription medication [34,58,67,72].…”
Section: Patterns Of MC Usementioning
confidence: 99%
See 1 more Smart Citation
“…On reviewing the published literature in detail, we found 3 previously published case reports over the last two decades, detailing 4 patient cases of adults using cannabis to reduce uncontrolled seizures . We also found 1 case series study, 7 RCTs, 1 observational study and 5 surveys examining the efficacy and safety of cannabis use in epilepsy. (Table S1) These studies showed a reduction or complete freedom from seizures following the use of CBD compared with placebo.…”
Section: Case Descriptionmentioning
confidence: 99%
“…3 In the absence of established clinical guidelines that stem from the paucity of clinical trial testing of MC products on the market, the adoption of MC as a therapy to manage symptoms associated with various chronic conditions continues to proliferate as an alternative or complementary method vis-àvis prescription medications. [4][5][6] To date, gender-related differences in MC use are not widely reported, and little is known about physicians' support of patients' use of MC to address symptoms associated with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%